2018
DOI: 10.1002/cam4.1327
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in breast phyllodes tumors: a nomogram based on a retrospective cohort study of 404 patients

Abstract: The aim of this study was to explore the independent prognostic factors related to postoperative recurrence‐free survival (RFS) in patients with breast phyllodes tumors (PTBs). A retrospective analysis was conducted in Fudan University Shanghai Cancer Center. According to histological type, patients with benign PTBs were classified as a low‐risk group, while borderline and malignant PTBs were classified as a high‐risk group. The Cox regression model was adopted to identify factors affecting postoperative RFS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 34 publications
3
26
1
Order By: Relevance
“…The medical histories of all patients were assessed to determine disease recurrence rates. Similar to previous reports, we found that the recurrence rate was 14.8%, and the mortality rate was 6.6% [2,3,5,8].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The medical histories of all patients were assessed to determine disease recurrence rates. Similar to previous reports, we found that the recurrence rate was 14.8%, and the mortality rate was 6.6% [2,3,5,8].…”
Section: Discussionsupporting
confidence: 91%
“…Compromised resection margins have also been linked to local and distant recurrence [14][15][16][17]. However, these rates were lower in our study than in previous reports [2,3,8]. Indeed, only one patient in the present study had compromised resection margins, and this patient experienced a local recurrence.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In 2009, the results of 13 studies were summarized: 12/50 patients (24%) with borderline PTs and 25/124 patients (20%) with malignant PTs locally recurred after margin-negative BCS. 2 [3][4][5][6][7] Combining these results with the 13 previous studies identified 140 LRs in 685 patients, a 20.4% LR rate in patients with borderline or malignant PTs undergoing BCS with negative margins.…”
supporting
confidence: 70%
“…First, our aim is to assess the prognostic value of clinicopathological characteristics in NEBC patients. Secondly, we designed to establish a predictive nomogram which has been wildly used in many other cancer diseases to accomplish overall survival estimation for NEBC patients [21][22][23][24][25][26][27]. Finally, we aimed to evaluate the clinical applicability of the nomogram in predicting prognosis.…”
Section: Introductionmentioning
confidence: 99%